PUBLIC ADMINISTRATION IN THE FIELD OF ECONOMIC SECURITY - Беззубов, Дмитро Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: to define the legal models of public administration of the system of ensuring economic security. Propose effective mechanisms for guaranteeing economic security. To suggest author's models of organizational support for the activities of public administration bodies. Methods: the study was conducted using classical methods of scientific knowledge. With the help of the method of analysis, the system elements of the legal mechanism of state control of the system of ensuring economic security are disclosed. With the help of the synthesis method, variants of the threat to economic security are considered. Results: according to the results of the study, mechanisms of effective state management of the system of ensuring economic security are proposed. Defined and disclosed components of organizational support for the process of making managerial decisions.